Evaluation of Adaptability of Different Cultivated Ecotypes of Saffron Under Maragheh Climatic Conditions - Amin Ensaf; Bahman Zahedi; Ali Asghar Aliloo (Zirā̒at va Fanāvarī-i Za̒farān, 2015)
In order to evaluate the adaptability of saffron ecotypes under Maragheh climatic conditions, an experiment was conducted based on a Randomized Complete Block design (RCBD) with three replications during the growing seasons of 2013 and 2014. The ecotypes used were Bardaskan, Abrud, Sabzevar, Bonab1, Torbat-e-Heydarieh, Bonab2, Marand1, Marand2, Kashmar, Taybad, Esfiukh and Mahvelat. The following traits were evaluated: fresh weight of stigma, dry weight of stigma, length of stigma, emergence percentage, emergence rate, flowering percentage, flowering rate, dry and fresh weight of flowers and dry yield of stigma in the area. The results showed that the ecotypes established very well in the first year of the experiment, but frosty days of the winter severely damaged Abrud, Taybad and Esfiukh ecotypes. There were significant differences among the ecotypes for the traits: the number of flowers, emergence, flowering percent and fresh weight of saffron. Also, a significant difference was recorded among the studied ecotypes for flowering and emergence rate. The highest emergence percentage was observed in Marand 2, while Sabzevar had the highest rate of flowering and flowering percentage. Despite the low yields for Marand1 and Sabzevar in the first year of the experiment, these ecotypes with 1.5 and 1.4 kg per hectare produced the high stigma yields, respectively in the second year. In conclusion, the results showed that the ecotypes of Marand are suitable for cultivate in the Maragheh climate conditions and the use of exotic corms is not recommended. Adaptability, Corm, Flowering percentage, Stigma yield